Buckeye, Dickinson County - Harlow, Kaitlyn (Kansas State University, The Chapman Center for Rural Studies, 2012)
It was a Tuesday, April 5, 1870, when a group of approximately two hundred people from Ohio emigrated to Buckeye Township, attracted by the promise of a homestead and prosperity. Residents faced many economic challenges over the years, and now only a cemetery remains.
Kaitlyn Harlow, “Buckeye, Dickinson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/144.
Keywords: Dickinson County; Cheese; Dairy; Great Depression; Homestead Act; Grasshoppers